Microglia Methods and Protocols - Joseph, Bertrand.; Joseph, Bertrand.; Venero, José Luis.; Venero, José Luis. (Methods in Molecular Biology, 2013)
Key discoveries concerning the different biological functions of microglia in health and disease have attracted scientists from various fields. In Microglia: Methods and Protocols, expert researchers in the field detail methods for selection of the key cellular, molecular and biochemical techniques that are used in studying the many and varied functions of this fascinating cell. These methods and techniques include microglia cell culture for studying microglia activation and functions, as well as their interaction with other cell types both in vitro and in vivo. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Microglia: Methods and Protocols is a useful resource for cell biologists, molecular biologists, immunologists, oncologist and neuroscientists.